MLA 7-94 - The Potential For Undiscovered Mineral Resources In The Absaroka-Beartooth Study Area (Part Of The Custer And Gallatin National Forests, Montana) - Len Blackman (The National Institute for Occupational Safety and Health (NIOSH), 1994)
The Absaroka-Beartooth Study Area is a tract of approximately 1.4 million acres of National forest land in southern Montana, part of the Greater Yellowstone Area. This study evaluated the mineral potential of four mineral terranes containing undiscovered resources in the area. The geological data is probabilistic, with estimates of the possible number: of deposits and their grades and tonnages. Possible future development scenarios range from no development to many mines, including some very large. As two thirds of the study area is within the Absaroka-Beartooth Wilderness, the future development scenarios reflect the area's mineral potential, not what we expect to see in the foreseeable future. Based on the analysis performed on these four terranes, the most likely future scenario for the study area would include the potential for two medium sized, (predominately) gold, mines, each employing a few hundred workers. There is a small chance, less than 5%, that a large Porphyry Copper or Superior Iron deposit would be discovered and be economically feasible to develop.